On the Reaction of 2-Alkanoylnaphthohydroquinones with Hydroxylamine: Access to Cytotoxic 2-(Hydroxyamino)-1, 4-naphthoquinone and Their 3-(Hydroxyimino)alkyl Analogous. (23rd August 2022) - Valderrama, Jaime A.; Pérez-Herrera, Andrea; Muccioli, Giulio G.; Venegas-Casanova, Edmundo A.; Jara-Aguilar, Rafael; Calderon, Pedro Buc; Benites, Julio
Abstract : Oximes are known for their anti-inflammatory, antimicrobial, antioxidant, and anticancer activities. Frequently, modification of biologically active carbonyl compounds into oximes leads to increased activity. The present study reports the reactivity of 2-alkanoylnaphthohydroquinones against hydroxylamine under aerial conditions. Results show that, depending on the structure of the hydroquinones, the reaction proceeds through two different chemical pathways to produce 2-(hydroxyamino)-1, 4-naphthoquinone and their C-3 (hydroxyimino)alkyl derivatives. Both the formation of the quinoid compounds under aerial oxidation and C-C cleavage reactions of hemiaminal intermediates are discussed. In vitro screening of the substituted 1, 4-naphthoquinones on a panel of cancer cells reveals moderate cytotoxic activities. Compound 19, 2-(hydroxyamino)-1, 4-naphthoquinone, stands out by its anticancer potency against prostate cancer cells as shown by the lowest IC50 value (8.08  μ M) and the best selectivity index (3.90).